MHD mixed convective Maxwell liquid flow passing an unsteady stretched sheet - Iswar Chandra Mandal; Swati Mukhopadhyay; Mani Shankar Mandal (Partial Differential Equations in Applied Mathematics, 2024)
This study is aimed to investigate the unsteady two-dimensional combined forced and natural convective motion of MHD Maxwell liquid passing a stretched surface. Non-Newtonian feature of the liquid is portrayed with the ‘upper convected Maxwell fluid’ model. A prearranged surface ‘temperature’ at the boundary is considered. ‘Similarity transformations’ are applied to find the self-similar solutions and then the altered ‘equations’ are numerically solved with the help of ‘Runge-Kutta method with shooting technique’. The behaviours of ‘flow’ and ‘heat’ transportation characters for diverse foremost ‘parameters’ are examined and discussed in detail for clear understanding about the non-Newtonian flow features and related thermal field. The interesting behaviours of flow and heat transfer characters warrant further studies of this problem for other type of situations. Due to unsteadiness, ‘velocity and temperature’ are seen to reduce for ‘buoyancy aided and opposed’ flows. Also, it is noted that for ‘buoyancy aided and opposed flows’, liquid velocity diminishes for rising ‘Hartmann number’. The influences of mounting ‘Maxwell parameter’ are to delay fluid velocity for either value of mixed convection parameter. However, for this case temperature is improved. Owing to mixed convection, liquid velocity increases but the temperature reduces within the ‘boundary layer’ area. Here lies the significance of the present study as this result is very much helpful for industrial applications for cooling purpose of different devices.